2020
DOI: 10.1021/acs.orglett.0c02144
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Radical–Radical Cross-Coupling Approach between Sodium Sulfinates and 2H-Indazoles to 3-Sulfonylated 2H-Indazoles

Abstract: A direct cross-coupling between sodium sulfinates and 2H-indazoles has been developed under electrochemical conditions. The utilization of a graphite anode and platinum cathode in an undivided cell with a constant current of 7 mA allowed the concurrent oxidations of sulfinates and 2H-indazoles to sulfonyl radical and radical cationic 2H-indazoles, facilitating the direct radical–radical coupling strategy to 3-sulfonylated 2H-indazole derivatives. The transition-metal- and redox-reagent-free synthetic approach … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
54
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(55 citation statements)
references
References 47 publications
1
54
0
Order By: Relevance
“…Undoubtedly, the addition of sulfonyl radicals to 8‐aminoquinolines as suggested by Waldvogel and others cannot be completely excluded [14b,c] . On the other hand, 8‐aminoquinolins 4 may be oxidized at the anode to form a radical cation and then generate C−S bond through radical/radical cross‐coupling with intermediate E [14d,f,15] …”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Undoubtedly, the addition of sulfonyl radicals to 8‐aminoquinolines as suggested by Waldvogel and others cannot be completely excluded [14b,c] . On the other hand, 8‐aminoquinolins 4 may be oxidized at the anode to form a radical cation and then generate C−S bond through radical/radical cross‐coupling with intermediate E [14d,f,15] …”
Section: Resultsmentioning
confidence: 97%
“…Waldvogel and co‐workers reported an electrochemical strategy for the synthesis of arylsulfones by direct sulfonylation of phenols with sodium sulfonates [14b,c] . Very recently, Oh, [14d] Lei [14e] and Wu [14f] reported the heteroarene sulfonaylation with sodium sulfinates via electrochemical methods (Scheme 1b). Li and Lei reported directed anodic C−H sulfonylation of N,N‐disubstituted anilines with sulfinates (Scheme 1c) [15] .…”
Section: Introductionmentioning
confidence: 99%
“…The results indicated that DLP is the best oxidant in this system. Then the solvents like H 2 O, glycerol, polyethyleneglycol (PEG 400 ), cyclopentyl methyl ether (CPME), 1,4-dioxane, MeCN, toluene, acetone, DMF, MeOH, EtOH, and DMSO were evaluated (entries [11][12][13][14][15][16][17][18][19][20][21][22]. The best result was afforded in H 2 O, which gave the desired product 3a in an improved yield (82%, entry 11).…”
Section: Resultsmentioning
confidence: 99%
“…8 Recently, the direct C3 functionalization of 2H-indazoles using radical reactions has gained great advances. For instance, the radical C3-functionalization of 2-aryl-2H-indazole including the C3-alkylation, 9 C3-benzylation, 10 C3-trifluoromethylation, 11 C3-acylation, 12 C3-arylation, 13 C3-amination, 14 C3-alkoxylation, 15 C3-sulfonylation, 16 C3-thiocyanation, 17 C3cyanoalkylation, 18 C3-phosphonylation, 19 C3-carbamoyla-tion, 20 C3-fluorination, 21 etc., was built up by cross-coupling of the radical sources and heteroaromatic substrates. Despite these significant advances, general methods for the C3ethoxycarbonylmethylation of 2H-indazole have not been established to date.…”
Section: Introductionmentioning
confidence: 99%
“…Oh and his co‐workers [55] reported a transition metal‐free electrochemical direct cross‐coupling approach for synthesis of a bunch of 3‐sulfonylated 2 H ‐indazole derivatives. The employment of a 7 mA constant current in an undivided cell with C‐anode and Pt‐cathode led to couple sulfinates 29 and 2 H ‐indazoles 46 via radical pathway to afford desired 3‐sulfnylated products 59 within 3 h at room temperature (Scheme 32).…”
Section: Electrochemical Functionalization Of Indazolementioning
confidence: 99%